Desperately seeking happy chickens: producer dynamics and consumer politics in quality agricultural supply chains. Issue 7 (3rd June 2020) - Carter, Elizabeth
Abstract : Purpose: The purpose of this paper is to understand why the quality markets are expanding in some areas of food production, while struggling in others. Across agricultural markets in advanced industrialized economies, there are movements toward quality production and consumption. The author argues that the quality turn in beer, coffee, wine and other transformed artisanal food production are fundamentally different from the quality movements in primary food products. The heart of that difference lies in the nature of the supply chain advantages of transformed versus primary agricultural products. Design/methodology/approach: The author applies convention theory to explain the dynamics within transformed agricultural quality markets. In these producer-dominant markets, networks of branded producers shape consumer notions of product quality, creating competitive quality feedback loops. The author contrasts this with the consumer-dominant markets for perishable foods such as produce, eggs, dairy and meat. Here, politically constructed short supply chains play a central role in building quality food systems. Findings: The emergence of quality in primary food products is linked to the strength of local political organization, and consumers have a greater role in shaping quality in these markets. Originality/value: Quality beer, coffee, wine and other transformed products can emerge without active political intervention, whereas quality markets for perishable foods are the outcome of political action. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-01-2020-0001 .